2016
DOI: 10.1089/ten.tec.2015.0291
|View full text |Cite
|
Sign up to set email alerts
|

T2 and Apparent Diffusion Coefficient of MRI Reflect Maturation of Tissue-Engineered Auricular Cartilage Subcutaneously Transplanted in Rats

Abstract: In cartilage regenerative medicine, autologous chondrocyte implantation (ACI) has been applied clinically for partial defects of joint cartilage or nasal augmentation. To make treatment with ACI more effective and prevalent, modalities to evaluate the quality of transplanted constructs noninvasively are necessary. In this study, we compared the efficacy of several noninvasive modalities for evaluating the maturation of tissue-engineered auricular cartilage containing a biodegradable polymer scaffold. We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…10 ). The findings resembled those of experimental transplantation in nude rats [18] . However, it appeared different from the morphology of repaired actual articular cartilage reported to show prominently high intensity on fsT2 images of MRI [10] .…”
Section: Discussionsupporting
confidence: 77%
“…10 ). The findings resembled those of experimental transplantation in nude rats [18] . However, it appeared different from the morphology of repaired actual articular cartilage reported to show prominently high intensity on fsT2 images of MRI [10] .…”
Section: Discussionsupporting
confidence: 77%
“…Comparing the T2 values among AC, EC, and SF groups, we con rmed that MRI could indicate the difference between normal cartilage, engineered elastic cartilage, and brous tissue. Moreover, the T2 value showed a better correlation with GAG and HYP contents of tissue-engineered cartilage, which was consistent with other studies (14,18,23). Especially, the T2 value showed a high coe cient of more than 0.88 with elastin content, suggesting the feasibility of MRI T2 mapping in evaluating engineered elastic cartilage.…”
Section: Discussionsupporting
confidence: 90%
“…The ECM of cartilage mainly consists of water (60-85% of wet weight) and macromolecules such as collagen bers and proteoglycan (12). Speci cally, T1 relaxation time was found to be highly correlated with the proteoglycan content, and water apparent diffusion coe cient (ADC) were found to re ect the total amount of collagen and proteoglycans (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported changes in T 2 and/or ADC values to be associated with other mechanisms like ECM architecture remodeling, [24][25][26][27] fibrous tissue formation, [28][29][30] tissue hydration, 26,[31][32][33] and inflammation, [34][35][36] which may occur concurrently with cellular infiltration and hence affect the T 2 and ADC values. Moreover, the relationship between total cellularity, T 2 , and ADC values has also been well documented in the cancer literature.…”
Section: Discussionmentioning
confidence: 99%